Near-horizon Polarization as a Diagnostic of Black Hole Spacetime - Yehui Hou; Jiewei Huang; Minyong Guo; Yosuke Mizuno; Bin Chen (The Astrophysical Journal Letters)
A key challenge in imaging supermassive black holes is disentangling gravitational effects from plasma physics in order to accurately determine spacetime properties, particularly black hole spin. In this Letter, we present a fully covariant and rigorous analysis of the synchrotron emission from accreting plasma in the equatorial plane in the stationary, axisymmetric, high-conductivity regime and identify—for the first time—a distinctive near-horizon polarization pattern that remains robust across different flow structures. This pattern arises from strong frame dragging near the event horizon, which induces a degeneracy among plasma flow and magnetic field configurations, yielding a polarization signature determined solely by the spacetime geometry and the observer’s inclination. The near-horizon polarization thus offers a clean and precise probe of black hole spin and other fundamental parameters. If future space-based millimeter very long baseline interferometry observations can resolve synchrotron emission originating within approximately 1% of the event horizon radius in M87* or Sgr A*, this universal polarization pattern may become observable.